Towards a definition of sustainable banking: A consolidated approach in the context of guidelines and strategies - Markus Riegler (International Journal of Corporate Social Responsibility (JCSR), 2023)
Sustainable development efforts, initiated by the SDGs and the Paris Agreement on climate change, are bringing banking to the center of the debate, which calls for, among other things, sustainable banking. In the current academic discussion, sustainable banking is described as a terminological jungle that is subject to change over time. Using Webster and Watson's conceptual model, this review analyzes the definitions and conceptual descriptions used in academia to present a consolidated result. The definition analysis conducted in this paper shows that definitions used mostly refer to the implementation of social, environmental aspects in the respective business strategies and / or to the offering of sustainably labeled products. This paper also shows that the various forms of the definition have a purely descriptive character and that measurability and comparability are hardly possible due to the lack of a generally accepted sustainability index.
Keywords: 650; Banking industry; Green banking; Social banking; Sustainability; Sustainable banking